Remineralization of artificial dentin lesion In vitro using dental nano-materials - Roshni U Rai; Ravi Ranjan; Mukesh Kumar; Uzma Mukri; Nutan Mala; Kunal Kumar (Wolters Kluwer Medknow Publications, 2021)
Background: Teeth in the human body are the most mineralized tissue, which contain both organic and inorganic components. Demineralization and remineralization of teeth occur continuously, but demineralization causes structural loss of a tooth. Aim: This study was done to find the effect of ceramic by adding mono-n-Dodecyl phosphate to ceramic in dentin remineralization. Materials and Methods: A total of sixty permanent intact tooth specimens were randomly divided into four equal groups: Group 1: control group, Group 2: dentin was etched and restored with plain ceramic restoration, Group 3: etched dentin restored with ceramic containing 2% mono-n-Dodecyl phosphate, and Group 4: etched dentin restored with ceramic containing 5% mono-n-Dodecyl phosphate. Each sample was immersed completely in simulated body fluid and was kept in an incubator at 37°C to simulate the human body environment. Knoop microhardness measurements were recorded at 10, 20, and 38 days. Results: Knoop microhardness of dentin (KHN) reduced to 32.6% after dentin was etched. No significant difference was found between group 2, 3 and 4 after 10 days. KHN value was increased and showed significant changes restored with group 2 and 3, group 3 showed nonsignificant changes. Conclusion: Through this study, we found that Ceramic can be used as a remineralizing agent to restore marginal dentine around of the cavity and root lesions from secondary caries.